recall in a perfect square trinomial, the middle term is the tale-tell guy, we know the middle term is the product of 2 and the two other guys without the exponent, so in this case 6x = 2*√x² * √c.
![\bf 6x=2\cdot \sqrt{x^2}\cdot \sqrt{c}\implies 6x=2\sqrt{x^2c}\implies 6x=2x\sqrt{c}\\\\\\\cfrac{6x}{2x}=\sqrt{c}\implies 3=\sqrt{c}\implies 3^2=c\implies 9=c](https://tex.z-dn.net/?f=%20%5Cbf%206x%3D2%5Ccdot%20%5Csqrt%7Bx%5E2%7D%5Ccdot%20%5Csqrt%7Bc%7D%5Cimplies%206x%3D2%5Csqrt%7Bx%5E2c%7D%5Cimplies%206x%3D2x%5Csqrt%7Bc%7D%5C%5C%5C%5C%5C%5C%5Ccfrac%7B6x%7D%7B2x%7D%3D%5Csqrt%7Bc%7D%5Cimplies%203%3D%5Csqrt%7Bc%7D%5Cimplies%203%5E2%3Dc%5Cimplies%209%3Dc%20)
Given data:
The given expression is 8 ⅓-5.
The given expression can be written as,
![\begin{gathered} 8\frac{1}{3}-5=\frac{25}{3}-5 \\ =\frac{25-15}{3} \\ =\frac{10}{3} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%208%5Cfrac%7B1%7D%7B3%7D-5%3D%5Cfrac%7B25%7D%7B3%7D-5%20%5C%5C%20%3D%5Cfrac%7B25-15%7D%7B3%7D%20%5C%5C%20%3D%5Cfrac%7B10%7D%7B3%7D%20%5Cend%7Bgathered%7D)
Thus, the difference of the given expression is 10/3.
Answer:
4 hours
Step-by-step explanation:
1+1=2
6-2=4
Answer:
f/2 is the answers for the question
Step-by-step explanation:
please mark me as brainlest
a.84
clickkkkk
lemme know if u need explanation